Differences in Presentation and Outcomes Between Children With Familial Dilated Cardiomyopathy and Children With Idiopathic Dilated Cardiomyopathy: A Report From the Pediatric Cardiomyopathy Registry Study Group. (February 2017) - Rusconi, Paolo; Wilkinson, James D.; Sleeper, Lynn A.; Lu, Minmin; Cox, Gerald F.; Towbin, Jeffrey A.; Colan, Steven D.; Webber, Steven A.; Canter, Charles E.; Ware, Stephanie M.; Hsu, Daphne T.; Chung, Wendy K.; et al.
Abstract : Background—: Research comparing the survival of children with familial dilated cardiomyopathy (FDCM) to that of children with idiopathic dilated cardiomyopathy (IDCM) has produced conflicting results. Methods and Results—: We analyzed data from children with FDCM or IDCM using the National Heart, Lung, and Blood Institute-funded Pediatric Cardiomyopathy Registry. Compared to children with IDCM (n=647), children with FDCM (n=223) were older (mean 6.2 versus 4.5 years, P <0.001), less often had heart failure (64% versus 78%, P <0.001), had less-depressed mean left ventricular fractional shortening z scores (−7.85±3.98 versus −9.06±3.89, P <0.001) and lower end-diastolic dimension z scores (4.12±2.61 versus 4.91±2.57, P <0.001) at diagnosis. The cumulative incidence of death was lower for patients with FDCM compared with IDCM ( P =0.04; hazard ratio 0.64, P =0.06), but no difference in risk of transplant or the combined death or transplant outcome. There was no difference in the proportion of children with echocardiographic normalization at 3 years of follow-up (FDCM, 30% versus IDCM, 26%; P =0.33). Multivariable analysis showed no difference in outcomes between FDCM and IDCM but for both groups older age, congestive heart failure, and increased left ventricular end-systolic dimension z score at diagnosis were independently associated with an increased risk of death or heart transplantation (all P s<0.001). Conclusions—: There was no survival difference between FDCM and IDCM after adjustment for other factors. Older age, congestive heart failure, and greater left ventricular dilation at diagnosis were independently associated with increased risk of the combined end point of death or transplantation. Clinical Trial Registration—: URL:https://clinicaltrials.gov . Unique identifier: NCT00005391